Virtual cell forming algorithm based on interference fair and multi-dimensional cooperation for ultra-dense network - Xiaoning ZHAO; Changyin SUN; Yanxia LIANG (Dianxin kexue)
Virtual cell is identified as one of factors affecting the system performance in ultra-dense network where the interference is complex with the increasing density of cells and the resource allocation strategies of different dimensions were coupled in overlapped virtual cells.Therefore,aiming at designing the edge weight of virtual cells,an algorithm considering the resource allocation in advance was proposed by taking interference fair power allocation,MU-MIMO operation and cooperative transmission into account simultaneously.Based on the proposed scheme of weight,the overlapped virtual cells could be formed by the proposed clustering algorithm named pairwise maximum weights.The simulation results demonstrate that the proposed algorithm can improve the sum-rate performance of the network effectively at a low complexity.